Robust RNA-based in situ mutation detection delineates colorectal cancer subclonal evolution. Issue 1 (December 2017) - Baker, Ann-Marie; Huang, Weini; Wang, Xiao-Ming; Jansen, Marnix; Ma, Xiao-Jun; Kim, Jeffrey; Anderson, Courtney; Wu, Xingyong; Pan, Liuliu; Su, Nan; Luo, Yuling; Domingo, Enric; et al.
Abstract Intra-tumor heterogeneity (ITH) is a major underlying cause of therapy resistance and disease recurrence, and is a read-out of tumor growth. Current genetic ITH analysis methods do not preserve spatial context and may not detect rare subclones. Here, we address these shortfalls by developing and validating BaseScope—a novel mutation-specific RNA in situ hybridization assay. We target common point mutations in theBRAF, KRAS andPIK3CA oncogenes in archival colorectal cancer samples to precisely map the spatial and morphological context of mutant subclones. Computational modeling suggests that subclones must arise sufficiently early, or carry a considerable fitness advantage, to form large or spatially disparate subclones. Examples of putative treatment-resistant cells isolated in small topographical areas are observed. The BaseScope assay represents a significant technical advance for in situ mutation detection that provides new insight into tumor evolution, and could have ramifications for selecting patients for treatment. Methods that analyze intra-tumor genetic heterogeneity often do not preserve the spatial context of tumor subclones. Here, the authors present BaseScope, a mutation-specific RNA in situ hybridization assay and spatially map colorectal cancer and adenomaKRAS, BRAF andPIK3CA driver gene mutant subclones.